The Royal Netherlands Football Association (KNVB) relative age solutions project - part two: an adapted e-Delphi study - Kelly, A. L.; Zwenk, F.; Mann, D.; Verbeek, J. (Frontiers in Sports and Active Living, 2025)
Introduction: Following the lack of widely implemented interventions to mitigate Relative Age Effects (RAEs) in sports, the Royal Netherlands Football Association (KNVB) called on stakeholders to propose relative age solutions in youth soccer (Part One). This initial study yielded 13 lower-order potential solutions, many of which remain hypothetical. Therefore, this study aimed to evaluate these solutions to overcome RAEs in youth soccer using a two-round adapted e-Delphi study.